Toll-Like Receptor 4 Modulates Small Intestine Neuromuscular Function through Nitrergic and Purinergic Pathways - Caputi, Valentina; Marsilio, Ilaria; Cerantola, Silvia; Roozfarakh, Mona; Lante, Isabella; Galuppini, Francesca; Rugge, Massimo; Napoli, Eleonora; Giulivi, Cecilia; Orso, Genny; Giron, Maria Cecilia (Frontiers in Pharmacology, 2017)
Objective Toll-like receptors (TLRs) play a pivotal role in the homeostatic microflora-host crosstalk. TLR4-mediated modulation of both motility and enteric neuronal survival has been reported mainly for colon with limited information on the role of TLR4 in tuning structural and functional integrity of enteric nervous system (ENS) and in controlling small bowel motility. Methods Male TLR4 knockout (TLR4-/-, 9±1 weeks old) and sex- and age-matched wild-type (WT) C57BL/6J mice were used for the experiments. Alterations in ENS morphology and neurochemical code were assessed by immunohistochemistry whereas neuromuscular function was evaluated by isometric mechanical activity of ileal preparations following receptor and non-receptor-mediated stimuli and by gastrointestinal transit. Results The absence of TLR4 induced gliosis and reduced the total number of neurons, mainly nNOS+ neurons, in ileal myenteric plexus. Furthermore, a lower cholinergic excitatory response with an increased inhibitory neurotransmission was found together with a delayed gastrointestinal transit. These changes were dependent on increased ileal non-adrenergic non-cholinergic (NANC) relaxations mediated by a complex neuronal-glia signaling constituted by P2X7 and P2Y1 receptors, and NO produced by nNOS and iNOS. Conclusions We provide novel evidence that TLR4 signaling is involved in the fine-tuning of P2 receptors controlling ileal contractility, ENS cell distribution, and inhibitory NANC neurotransmission via the combined action of NO and ATP. For the first time, this study implicates TLR4 at regulating the crosstalk between glia and neurons in small intestine and helps to define its role in gastrointestinal motor abnormalities during dysbiosis.